2017
DOI: 10.2340/16501977-2189
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cognitive behavioural therapy in a community-based pulmonary rehabilitation programme: A controlled clinical trial

Abstract: The addition of cognitive behavioural therapy improved patients' physical, psychological and quality of life results. Cognitive behavioural therapy should be considered for inclusion in a pulmonary rehabilitation programme to enhance outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…As demonstrated in previous studies (174,175), our study showed a significant improvement in GDS by the end of rehabilitation for both the Control and Intervention group; however, the Intervention group seemed to have a larger although modest reduction in mean GDS of 3.1 (almost 50% of baseline score) compared to the Control group (1.34) and although there was a trend it did not reach statistical significance (p = 0.053). Interestingly, there was an overall improvement in GDS in almost all patients that attended CBT, while the control group showed that approximately 2/3 of the patients improved (Figure 4).…”
Section: Effects Of Cbt On Depressionsupporting
confidence: 68%
See 4 more Smart Citations
“…As demonstrated in previous studies (174,175), our study showed a significant improvement in GDS by the end of rehabilitation for both the Control and Intervention group; however, the Intervention group seemed to have a larger although modest reduction in mean GDS of 3.1 (almost 50% of baseline score) compared to the Control group (1.34) and although there was a trend it did not reach statistical significance (p = 0.053). Interestingly, there was an overall improvement in GDS in almost all patients that attended CBT, while the control group showed that approximately 2/3 of the patients improved (Figure 4).…”
Section: Effects Of Cbt On Depressionsupporting
confidence: 68%
“…However, this was modest in our rehabilitation program -entailing a 1-hour session in problem-solving, and a basic education session regarding the association of anxiety and depression with chronic lung disease (Appendix 1). The dampening effect of pulmonary rehabilitation may have been present in another recent similar study, which used 6 sessions of groupbased CBT given with a similar pulmonary rehabilitation program (175). Our study had an intention-to-treat analysis that may have also had a dampening effect in assessing improvement in GDS, caused by the significant withdrawal rate in the study.…”
Section: Effects Of Cbt On Depressionmentioning
confidence: 92%
See 3 more Smart Citations